Enhancement of physical and mechanical properties of polyamide 66 fibers using polysiloxane‐functionalized multi‐walled carbon nanotubes. Issue 14 (16th November 2020) - Zhang, Jiao; Yu, Wenguang; Zhang, Xianye; Gao, Xuefeng; Liu, Haihui; Zhang, Xingxiang
Abstract: A polyamide 66/3‐aminopropyl‐terminated poly(dimethylsiloxane) (PA66/APDMS)‐carboxylate multiwalled carbon nanotubes (CMWNTs) nanocomposite (PA66/APDMS‐CMWNTs) was synthesized using a one‐pot method, and the product was melt‐spun into fibers. The glass transition temperature ( T g ) of the PA66/APDMS‐CMWNTs nanocomposite fiber is 68.0°C, which is 22% higher than that of the pure PA66 fiber. This result indicates that there is a strong interfacial interaction between APDMS‐CMWNTs and the PA66. Furthermore, the crystallinity of PA66/APDMS‐CMWNTs nanocomposite fiber reaches a maximum due to the addition of APDMS‐CMWNTs. Additionally, the tensile strength and Young's modulus of PA66/APDMS‐CMWNTs nanocomposite fiber are 167% and 631% higher, respectively, than that of the pure PA66 fiber. The strengthening mechanism was discussed using force balance‐based expression, which demonstrates that the stress on the PA66 is more efficiently transferred to the APDMS‐CMWNTs. These results argue that using APDMS‐CMWNTs as a filler can enhance the physical‐mechanical properties of PA66 with an elevated degree never being reported. Abstract : The surface of (a) PA66/CMWNTs and (b) PA66/APDMS‐CMWNTs fiber. Polymer crystallinity induced by each carbon nanotube can propagate for a distance from the nanotubes surface in (a), but the polymer crystallinity induced by APDMS‐CMWNTs make spread a greater distance from the surface of the carbon nanotube in (b). This result confirms that the interfacial interaction between APDMS‐CMWNTs and PA66 is stronger than that of CMWNTs and PA66. Thereby the APDMS functionalized CMWNTs sample can effectively improve the mechanical properties of the composite fibers